"— It would be possible to do a lengthy dialectical number on this;". (August 2020) - Myrvold, Wayne C.
Abstract: Philosophers have, it seems, been beguiled by contingencies of the evolution of scientific language. These contingencies can obscure the nature of theoretical shifts. Retention of a term can obscure a radical theoretical shift, and abandonment of a term can obscure continuity of theory. In this paper, I consider the cases of caloric and the luminiferous ether, both of which are often taken to be unproblematic cases of theoretical entities abandoned by subsequent theories. I invite the reader to consider what we might now be saying were those terms retained, and argue that this sheds light on the nature of the theoretical shifts involved.. Highlights: Philosophers have, in certain cases, been beguiled by contingencies of evolution of scientific language. Caloric and the luminiferous ether are cases in point. These are often regarded as unproblematic cases of theoretical entities abandoned by subsequent theories. Things are not so simple! It is worthwhile examining what we would now be saying had those terms been retained.